The Necessity of Immigration of Information Competences to Students (Eurasian Journal of Learning and Academic Teaching, 2023)
In the article, information competence refers to the ability and skills of a person to perform certain labor activity tasks required for effective work in the future or in the information-professional field, and in some cases, information competence is a person's professionalism, professional ethics, manners of receiving information, information Opinions were expressed regarding the high level of culture of reception